Biogeographic patterns and environmental drivers of species richness in the globally distributed Millettioid/Phaseoloid clade (Fabaceae, subfamily Papilionoideae) - Oyebanji, Oyetola O.; Onditi, Kenneth O.; Azevedo, Josué A. R.; Rahaingoson, Fabien R.; Nneji, Lotanna M.; Adeleye, Matthew. A.; Stull, Gregory W.; Zhang, Rong; Yi, Ting-Shuang (Frontiers in Ecology and Evolution, 2023)
The Millettioid/Phaseoloid (MP) clade of the Fabaceae family is globally distributed, economically important, and highly diverse, making it an attractive system for studying biogeographic and macroecological patterns at a global scale. To this end, geospatial analyses were performed to estimate species richness patterns, biogeographic heterogeneity, and the effects of environmental variables on the species richness using global species occurrences for the MP clade (116,212 occurrence points) and 20 environmental variables (19 bioclimatic variables and elevation). Our study identified the megathermal regions as hotspots of species richness for the MP clade. While species distributions and richness largely fit the latitudinal diversity gradient pattern, there was a significant negative relationship between the species richness of the MP clade along the latitude and longitude. The Afrotropic biogeographic realm has the highest α-diversity (~ 36%); in terms of biome types, tropical and subtropical moist broadleaf forests had the highest α-diversity (25%), while the β-diversity indicates a high dispersal rate and habitat tracking. Furthermore, the MP clade was positively influenced by Macroecology of the MP clade multiple climatic factors, with the mean diurnal range of temperatures (BIO2) and precipitation in the warmest quarter (BIO18) having strongest influence. Overall, the staggering species richness patterns could be explained by multiple hypotheses consistent with the existing theories and climatic gradients. Particularly colder climates play a crucial role in shaping the species richness pattern by limiting the ecological opportunities for MP clade species in the higher latitudes of the Northern Hemisphere. This suggests that the species richness patterns of the MP clade can be described as "when dispersal meets adaptation." Our study provides a new basis for identifying priority regions for conservation under climate gradient scenarios.